2005
DOI: 10.1111/j.1742-4658.2005.04914.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced apoptosis through farnesol inhibition of phospholipase D signal transduction

Abstract: Farnesol is a catabolite of the cholesterol biosynthetic pathway that preferentially causes apoptosis in tumorigenic cells. Phosphatidylcholine (PC), phosphatidic acid (PA), and diacylglycerol (DAG) were able to prevent induction of apoptosis by farnesol. Primary alcohol inhibition of PC catabolism by phospholipase D augmented farnesol‐induced apoptosis. Exogenous PC was unable to prevent the increase in farnesol‐induced apoptosis by primary alcohols, whereas DAG was protective. Farnesol‐mediated apoptosis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 48 publications
0
24
0
1
Order By: Relevance
“…Indeed, it was previously shown by 31 P-NMR spectroscopy that induction of apoptosis by farnesol resulted in increased level of CDPC in favor of CPT blockade and the accumulation of fructose-1,6-bisphosphate, a glycolysis derivative, in favor of glycolysis downregulation. Second, DAG decrease could result from decreased hydrolysis of phospholipids, such as PtC via the inhibition of phospholipase C or D activity, as shown for farnesol cytotoxicity [36,37]. Third, CPT blockade may also be due to a rerouting of DAG through the activation of protein kinase C (PKC) or diacylglycerol kinase (DGK).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it was previously shown by 31 P-NMR spectroscopy that induction of apoptosis by farnesol resulted in increased level of CDPC in favor of CPT blockade and the accumulation of fructose-1,6-bisphosphate, a glycolysis derivative, in favor of glycolysis downregulation. Second, DAG decrease could result from decreased hydrolysis of phospholipids, such as PtC via the inhibition of phospholipase C or D activity, as shown for farnesol cytotoxicity [36,37]. Third, CPT blockade may also be due to a rerouting of DAG through the activation of protein kinase C (PKC) or diacylglycerol kinase (DGK).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were exposed to 5 lM DTX, 1 nM DTX, or the vehicle (0.5% DMSO) for 6,12,16,24,36,48,72, and 96 h. After each treatment and before analysis, cells were washed twice with PBS (100 ll per well or 10-20 ml per flask) to remove detached and dead cells. The pH of each medium was measured.…”
Section: Cell Treatmentmentioning
confidence: 99%
“…4 Therefore, generation of ROS by FOH may result in the activation of the ERK1/2 pathway and subsequently trigger the ER stress response. However, activation of the ERK1/2 pathway might be related to other actions of FOH, including inhibition of the CDP-choline pathway (5,20,21,48) and inhibition of phospholipase D (22) or HMG CoA reductase activity (6). Future studies have to provide insight into the mechanism by which FOH activates the MEK-ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Isoprenoids have been reported to inhibit posttranslational protein prenylation (19) whereas other studies have shown that FOH is a potent inhibitor of the CDP-choline pathway (5,20,21). Other effects include inhibition of phospholipase D (22), inhibition of 3-hydroxy-3-methylglutaryl CoA reductase (HMG CoA reductase) activity (6), generation of reactive oxygen species (ROS; refs. 23,24), and disorganization of the cytoskeleton (4).…”
Section: Introductionmentioning
confidence: 99%
“…albicans e A. nidulans (Voziyan et al, 1995;Yang e Kazanietz, 2003;Taylor et al, 2005;Fairn et al, 2007;Uppuluri et al, 2007;Savoldi et al, 2008;Román et al, 2009). A expressão constitutiva de Pkc1 leva a resistência de S. cerevisiae frente à presença de farnesol, possivelmente pela atividade na regulação da produção de espécies reativas de oxigênio (EROs) na cadeia de transporte de elétrons da mitocôndria (Fairn et al, 2007).…”
Section: -Peptídeo Sinal E Via Secretóriaunclassified